Future algorithm for optimised path selection and detection in MANET. (22nd August 2019) - Palanisamy, Ramesh; Mathivanan, V.
The beginning of wireless communication gives birth to cognitive radio mobile ad hoc networks (CRAHNs). Routing is the main factor in both wired and wireless networks. Three major types of routing can be performed in CRAHNs such as proactive, reactive and hybrid. This research work aims in design and development of a hybrid protocol named efficient zone-based routing protocol shortly termed as EZBRP, SACBRP and BIABRP. NS2 simulation tool is used to examine the performance of the proposed protocols. Communicating systems use well-defined formats (protocol) for exchanging various messages. Efficient zone-based routing protocol (EZBRP), spectrum aware cluster-based routing protocol (SACBRP), bee inspired agent-based routing protocol (BIABRP). This research on optimised path selection and detection in MANET and a considerable research effort is still required for secured communication.